The level of wasting and associated factors among children aged 6–59 months in sub-Saharan African countries: multilevel ordinal logistic regression analysis - Asebe, Hiwot Altaye; Asmare, Zufan Alamrie; Mare, Kusse Urmale; Kase, Bizunesh Fantahun; Tebeje, Tsion Mulat; Asgedom, Yordanose Sisay; Shibeshi, Abdu Hailu; Lombebo, Afewerk Alemu; Sabo, Kebede Gemeda; Fente, Bezawit Melak; Bezie, Meklit Melaku; Seifu, Beminate Lemma (Frontiers in Nutrition, 2024)
Background: Despite various interventions to combat child malnutrition in sub-Saharan Africa is, wasting remains a serious public health concern for children aged 6-59 months. Wasting is a significant predictor of child survival and development, with a heightened risk of mortality among children. However, there is a lack of recent comprehensive data on the prevalence, severity level, and factors contributing to wasting in this age group. Objective: to identify the severity levels of wasting and its individual and community-level factors contributing to wasting among children aged 6 to 59 months in Sub-Saharan African countries. Methods: This research utilized Demographic and Health Survey data from 34 Sub-Saharan African countries, spanning the period from 2007 to 2022. The study included a weighted sample of 180,317 6 to 59-month-old children. We employed a multilevel proportional odds model to identify factors predicting the severity of wasting. Adjusted odds ratios and 95% confidence intervals were reported to demonstrate significant relationships (p<0.05) in the final model. Results: In Sub-Saharan Africa, 7.09% of children aged 6 to 59 months experience wasting (95% CI: 6.97%, 7.20%). Among these children, the prevalence of moderate wasting is 4.97% (95% CI: 4.90%, 5.10%), while severe wasting affects 2.12% (95% CI: 2.0%, 2.20%). Factors such as term/post-term babies, wealth, frequency of feeding, improved toilet facilities, water sources, employed and educated mothers, rural residence, high community maternal education, and community media exposure are strongly associated with a lower chance of experiencing severe form of wasting. Conversely, birth order, family size, breastfeeding, diarrhea, cough, and fever, high community poverty, female household heads, and all Sub-Saharan Africa regions are linked to higher levels of wasting. Conclusion: The study findings underscore the persistent challenge of wasting among Sub-Saharan Africa’s children, with 7.09% affected, of which 4.97% experience moderate wasting and 2.12% severe wasting. The identified predictors of wasting highlight the complex interplay of socio-economic, environmental, and health-related determinants. To address this issue improve access to healthcare and nutrition services, enhance sanitation infrastructure, promote women's empowerment, and implement community-based education programs. Additionally, prioritize early detection through routine screening and strengthen health systems' capacity to provide timely interventions.